MODULUS RESILIENT AND DEFORMATION PERFORMANCE OF ASPHALTIC CONCRETE ÃâÃâ BINDER COURSE (AC-BC) USE OF RECYCLED MATERIAL AND ASPHALT MODIFIED ELFALOY - ZURNI (NIM : 269 10 302), RAHMI
Due to the limitation of natural agregate for asphalt pavement, the technology using recycled materials is one alternative to solve the problem. The objective of this research is to use the Recycled Asphalt Pavement (RAP) materials in AC-BC (Asphalt Concrete Binder Course) mixes, blending with asphalt Pen 60/70 and modified binder Elvaloy. The percentage of RAP materials is limited at 7,5% and 10%, considering the penetration value of blending result of those materials with aspal pen 60/70 and modified binder “limited” was about 50. For the same reason, the blend between modified binder “Elvaloy” and asphalt pen 60/70 was determined at 50% to 50% (by weight). The Laboratory testings conducted in this research were an Marshall test, Marshall Immersion, Resilient Modulus UMATTA and Wheel Tracking test. The result of UMATTA test give the highest Resilien Modulus for A1 mix, at two temperatur (25oC and 35oC). Those results were confirmed by the value of Marshall Stability. The result Modulus ratio between UMATTA test and the formula proposed by Shell and Nottingham, gave the small value, i.e. 1,23 and 0,94 respectively. This ratio indicates that the two methods could predict the Resilient Modulus of Asphalt Mix with a good accuracy. In general, the A1 mix (7,5% RAP and modified binder Elvaloy) gave the best result comparing with the other mixes (A2, B1 and B2 mixes), because the A1 mix has the highest Resilient Modulus (3593 MPa) and highest Dynamic Stability resulting from Wheel Tracking test (5250 T/mm)